(untitled) (Semiárida, 2026)
In recent decades, several wild vertebrate species have increased their presence in agroecosystems, exploiting food resources and generating negative impacts on agricultural production in Argentina. Birds and mammals exhibit a high capacity to adapt to novel environments, often resulting in significant production losses. This study evaluated the damage caused by the red-bellied squirrel and the monk parakeet in three pecan orchards located in Mercedes and one in Lobos (Buenos Aires Province, Argentina) during the autumn–winter season of 2023, considering two phenological stages of the crop: fruit filling stage and harvest. The occurrence and abundance of red-bellied squirrels and monk parakeets were assessed through trapping and direct counts, identifying both species as the sole agents responsible for the observed damage. Damage type was characterized based on morphological traits of fruit consumption and quantified as the percentage of damaged fruits, complemented by estimates of biomass loss expressed as kilograms of nuts per tree. Results showed that both species caused substantial production losses. Red-bellied squirrels primarily consumed the kernel during the harvest stage, causing an average damage of 18.7 % (SD= 15.8), with no significant differences in damage magnitude among orchards where squirrel damage was recorded (Kruskal–Wallis H= 0.22, p> 0.05). In contrast, monk parakeets mainly affected fruits during the filling stage by damaging the husk and inducing premature fruit drop, resulting in an average damage of 14.45 % (SD= 16.93), which was significantly lower in Lobos (0.35 %, SD= 0.56; H= 15.74, p< 0.05). Differences in both the magnitude and timing of damage revealed contrasting feeding strategies between the two species. Furthermore, fruit availability per tree was positively correlated with the level of damage recorded (Spearman: Rsquirrels= 0.85; p< 0.001; Rparakeets= 0.52; p < 0.05). These results highlight the need to implement species-specific and temporally adjusted management measures, considering crop phenology and the activity patterns of each species.